HER2-Testung beim Magenkarzinom: Ergebnisse eines deutschen Expertentreffens = HER2 testing in gastric cancer : results of a Germanexpert meeting - Lordick, Florian; Hofheinz, Ralf-Dieter; Gaiser, Timo (Zeitschrift für Gastroenterologie, 2016)
Valid HER2 testing is essential for optimal therapy of patients with HER2 positive gastric cancer and the correct use of first-line treatment. While each breast cancer is routinely being tested for the HER2 status, HER2 testing in gastric cancer has still not become part of the routine and is often only done upon request by the therapist. An interdisciplinary German expert group took the challenges of HER2 testing in gastric cancer as an opportunity to address essential aspects and questions for the practical use of HER2 testing in this indication from the perspective of pathologists and therapists. The recommendations made in this manuscript reflect the consensus of all participants and correspond to their opinions and long-term experience.